Effects of the sperm DNA fragmentation index on the clinical and neonatal outcomes of intracytoplasmic sperm injection cycles - Linjun Chen; Junshun Fang; Weihua Jiang; Jie Wang; Dong Li (Journal of Ovarian Research, 2020)
Abstract Background Most studies have mainly focused on the effects of the sperm DNA fragmentation index (DFI) on fertilization, embryonic developmental potential and aneuploidy, pregnancy and abortion rates after in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) and have remained controversial. However, few studies have reported the effects of sperm DFI on neonatal outcomes, including stillbirths, neonatal deaths, sex, gestational age, prematurity, birthweight, low birth weight (LBW) and birth defects in newborns. Our objective was to evaluate the effects of sperm DFI on the clinical and neonatal outcomes of ICSI cycles. Methods This retrospective study analysed a total of 2067 oocyte retrieval, 1139 transfer and 713 delivery cycles from conventional ICSI cycles, including 301, 469, and 214 live-born infants in groups segregated according to sperm DFI as the < 15%, 15–30% and >  30% groups, respectively. The clinical and neonatal outcomes were compared among the three groups. Results Sperm DFI did not significantly affect the rates of fertilization, clinical pregnancy, miscarriage or ongoing pregnancy. Sperm DFI did not increase the risk of stillbirths or neonatal deaths. The rates of stillbirths and neonatal deaths were not significantly different among the three groups. The sex, gestational age, prematurity, birthweight and LBW of newborns in the three groups were not significantly affected by sperm DFI. Moreover, sperm DFI did not increase the number of birth defects in children. Conclusions Sperm DFI did not affect the clinical or neonatal outcomes of ICSI cycles.